Pengaruh Employee Engagement, Disiplin Kerja Dan Gaya Kepemimpinan Transformasional Kepala Desa Terhadap Kinerja Perangkat Desa Dengan Komitmen Organisasi Sebagai Variabel Intervening (Survey Terhadap Perangkat Desa Se-Kecamatan Cidahu Kabupaten Kuningan) - Syakiroh; Harjadi, Dikdik; Djuniardi, Dede (Entrepreneur: Jurnal Bisnis Manajemen dan Kewirausahaan, 2024)
This research phenomenon is oriented towards the performance of village apparatus in Cidahu District, Kuningan Regency. The population of this study was all village apparatus in Cidahu District, Kuningan Regency, totaling 135 employees. Given the relatively small population, all populations were used as samples in this study, totaling 135 village apparatus in Cidahu District, Kuningan Regency. The results of the study were that employee engagement had a positive and insignificant effect on organizational commitment. Work discipline and transformational leadership style of the village head had a positive and significant effect on organizational commitment. Employee engagement and work discipline had a positive and significant effect on the performance of village apparatus. The transformational leadership style of the village head had a negative and insignificant effect on the performance of village apparatus. Organizational commitment had a positive and insignificant effect on the performance of village apparatus. Organizational commitment is unable to mediate the influence of employee engagement, work discipline and transformational leadership style on the performance of village officials.